Model Pengambilan Keputusan Kolaboratif dalam Meningkatkan Profesionalisme Guru: Penelitian - Putra, Mija Indra; Bakti, Irfan Prima; Marsidin, Marsidin; Irsyad, Irsyad (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the collaborative decision-making model in improving teacher professionalism at SMA Negeri 9 Mandau. Collaborative decision-making is a managerial approach that emphasizes the involvement of all parties in determining school policies. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results show that the principal and teachers involve all elements such as the vice principal, the head of the MGMP, and administrative staff in the process of formulating important decisions. The positive impact of implementing this collaborative model is an increased sense of responsibility, trust, and teacher participation in school activities. However, a negative impact was also found in the form of long decision-making time due to the many parties that must be consulted. This study concludes that collaborative decision-making is effective in improving teacher professionalism, as long as it is balanced with good coordination and time management.